Why do employees actively work overtime? The motivation of employees’ active overtime in China - Tan, Jinke; Zhang, Chunsheng; Li, Zhengyang (Frontiers in Psychology, 2023)
Introduction Previous studies have defined “workaholic” effort as “bad effort” while work engagement is defined as “good effort.” Active overtime is a mapping of work effort, but at this stage there is still relatively little exploration of the motivation behind “good effort” in the Chinese context. Methods This study explores the reasons that promote employees’ initiative to perform overtime work in Chinese enterprises based on the two-factor theory. The study mainly used data empirical research approaches, including exploratory factor analysis, validation factor analysis, and data modeling. The questionnaire scale was developed based on factors that have been proven to be of high reliability and validity. The data are mainly for employees who are currently employed in Chinese companies. Results and discussion We received a total of 1741 valid questionnaires, which provided a good database for this study. The results of the study show that both motivational and hygiene factors can positively promote employees’ motivation to intentionally work overtime to a certain extent. Among them, overtime culture, institutional agreement, good physical office environment, career growth, financial rewards, and work challenges can positively promote motivation to work overtime. Work stress can increase the frequency and intensity of overtime work, but negatively promote motivation to work overtime. The study helps to improve enterprise management, optimize work design, and enhance psychological satisfaction.